Students for Peace: Contextual and Framing Motivations of Antiwar Activism - Fahs, Breanne (2011)
This article traces the development of peace activism among undergraduate social work students. In doing so, it explores how social statuses, political contexts, and collective action frames affect the likelihood of joining the movement against the Afghanistan war (2001 to current). After analyzing data from a multicampus sample of Bachelors in Social Work (BSW) students (n = 159), results show that peace activism was predicted by level of education as well as perceptions of proper foreign policy, the relative efficacy of social movement tactics, and identification with specific activist ideals. Finally, being situated in activist networks fostered greater peace activism while the ascribed statuses of race, class, and gender were poor predictors of peace activism